Impact of immunosuppressive regimens on antibody response after COVID-19 vaccination among Thai kidney transplant recipients - Nuttasith Larpparisuth; Kritsada Pongsakornkullachart; Nartsiri Ratchawang; Attapong Vongwiwatana; Peenida Skulratanasak (Heliyon)
Background: The lower humoral immunity response after the COVID-19 vaccine in kidney transplant recipients (KTR) has been reported in several studies. However, there are few studies on the efficacy of the ChAdOx1 nCoV-19 (AstraZeneca) vaccine compared between various immunosuppressive regimens. Methods: We conducted a prospective cohort study at Siriraj Hospital, Bangkok, Thailand. Adult KTRs who received two doses of the ChAdOx1 nCoV-19 vaccine at intervals of 3 months were enrolled. Anti-SARS-COV-2 S-RBD-IgG antibody (anti-RBD) was assessed at the one month after the second dose and considered positive if the level ≥50 AU/mL or 7 BAU/mL. The primary outcome was the seropositivity of anti-RBD. The association between type, dose, and level of immunosuppressive regimen and anti-RBD seropositivity was analyzed. Results: Between October 2021 and January 2022, 139 KTRs with a median time of 55 months (IQR, 29–102 months), were enrolled. The mean age was 49.1 ± 11.3 years and 64.7 % were men. Seroconversion of anti-RBD was found in 72 patients (51.8 %). The seropositive rate was significantly higher in KTR who received tacrolimus (TAC)/everolimus (EVR)/prednisolone (CS) immunosuppression than EVR/mycophenolic acid (MPA)/CS and TAC/MPA/CS, respectively (95 % vs. 65 % vs. 34 %; p < 0.001). The MPA-containing regimen is associated with an inferior humoral response (OR 0.02, 95%CI 0.01–0.16; p < 0.001). In contrast, KTRs who received EVR had the highest immunogenic response (OR 12.97, 95%CI 4.69–35.84; p < 0.001). During the 11-month follow-up period, COVID-19 pneumonia occurred in 3 KTR in the seronegative group and none in the seropositive group. Conclusion: The anti-RBD response after ChAdOx1 nCoV-19 vaccination was revealed in 51.8 % of the KTR. KTRs who received the TAC/EVR/CS regimen had the highest immune response after vaccination, relatively comparable to the general population. The immunosuppressive regimen should be considered for a further vaccine dose in KTR.